Occupational Disruptions Among Health Professional Graduate Students During COVID-19 Pandemic - Supawadee C. Lee; Blerta Blushi; Joy Ann Dimaculangan; Anahid Keshishian; Michelle Segovia (Scholarworks @ WMU, 2022)
The COVID-19 pandemic created a global lockdown and restricted people from leaving their homes. The current study aimed to explore the impact of the pandemic on occupational engagement among health professional graduate students. A web-based survey consisting of quantitative and qualitative responses was sent out to graduate students enrolled in health professional programs at a private university in the Northeast and received 86 responses. The results revealed that social participation and education were the most impacted occupations. The least affected occupations among the graduate students in health professional programs was ADLs. The participants reported the pandemic did not negatively affect their grades or grade point average. Four themes emerged from the qualitative data: sedentary lifestyle, engaging in leisure activities, seeking support from friends and family, and interrupted clinical experience. The findings offer some insights into the needed support and resources universities and health professional programs can prepare and provide to students during the pandemic or future crises.